Dynamic regimes of neocortical activity linked to corticothalamic integrity correlate with outcomes in acute anoxic brain injury after cardiac arrest. Issue 2 (6th January 2017) - Forgacs, Peter B.; Frey, Hans‐Peter; Velazquez, Angela; Thompson, Stephanie; Brodie, Daniel; Moitra, Vivek; Rabani, Leroy; Park, Soojin; Agarwal, Sachin; Falo, Maria Cristina; Schiff, Nicholas D.; Claassen, Jan
Abstract: Objective: Recognition of potential for neurological recovery in patients who remain comatose after cardiac arrest is challenging and strains clinical decision making. Here, we utilize an approach that is based on physiological principles underlying recovery of consciousness and show correlation with clinical recovery after acute anoxic brain injury. Methods: A cohort study of 54 patients admitted to an Intensive Care Unit after cardiac arrest who underwent standardized bedside behavioral testing (Coma Recovery Scale – Revised [CRS‐R]) during EEG monitoring. Blinded to all clinical variables, artifact‐free EEG segments were selected around maximally aroused states and analyzed using a multi‐taper method to assess frequency spectral content. EEG spectral features were assessed based on pre‐defined categories that are linked to anterior forebrain corticothalamic integrity. Clinical outcomes were determined at the time of hospital discharge, using Cerebral Performance Categories (CPC). Results: Ten patients with ongoing seizures, myogenic artifacts or technical limitations obscuring recognition of underlying cortical dynamic activity were excluded from primary analysis. Of the 44 remaining patients with distinct EEG spectral features, 39 (88%) fit into our predefined categories. In these patients, spectral features corresponding to higher levels of anterior forebrain corticothalamic integrity correlated with higher levels of consciousness and favorable clinical outcome at the time of hospital discharge ( P = 0.014). Interpretation: Predicted transitions of neocortical dynamics that indicate functional integrity of anterior forebrain corticothalamic circuitry correlate with clinical outcomes in postcardiac‐arrest patients. Our results support a new biologically driven approach toward better understanding of neurological recovery after cardiac arrest.